Effectiveness of Multiple Representation-Based Mechanics Lectures Using YouTube Video Content on Concept Mastery - Hartini, Tri Isti; Ermawati, Imas Ratna; Martin, Martin; Sari, Nuraeni Nanda; Septiyani, Nunik Dwi; Sagita, Elsa (Universitas PGRI Semarang, 2024)
In mechanics lectures there are many abstract concepts. The existence of abstract concepts creates misperceptions among students. This research aims to determine the effectiveness of Multiple Representation-based mechanics lectures using YouTube video content on concept mastery. This research was conducted at the Physics Education Study Program, FKIP UHAMKA. The respondents in this study were 3rd semester students who were taking a mechanics course. This research uses a pre-experimental design method with a one group pretest-posttest research design. The results of the research show that the use of YouTube video content in multiple representation-based mechanics lectures is quite effective in increasing respondents' mastery of concepts. This can be seen from the post-test results of respondents, the majority of whom experienced an increase with an average score of 63 with the N - Gain score obtained having an average increase of 46.78% or in the medium category. The benefit of this research is knowing the respondent's level of concept mastery.